2008
DOI: 10.1029/2007gl031651
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Ocean surface warming trends over the past 100 years

Abstract: Ocean temperature profiles and satellite data have been analyzed for summertime sea surface temperature (SST) and upper ocean heat content variations over the past century, with a focus on the Arctic Ocean peripheral seas. We find that many areas cooled up to ∼0.5°C per decade during 1930–1965 as the Arctic Oscillation (AO) index generally fell, while these areas warmed during 1965–1995 as the AO index generally rose. Warming is particularly pronounced since 1995, and especially since 2000. Summer 2007 SST ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
297
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 371 publications
(310 citation statements)
references
References 36 publications
12
297
0
1
Order By: Relevance
“…In recent years, a drastic decrease in sea ice has been reported for the western Arctic Ocean during the summer months, and even greater related changes in sea surface temperatures have been reported (Stroeve et al, 2007;Steele et al, 2008). The changes in sea surface temperatures, increases in the frequency and intensity of cyclones, and northward shifts from their tracks during the summer months as well as during other seasons have also been reported (Serreze et al, 2000;McCabe et al, 2001;Sepp and Jaagus, 2011).…”
Section: Introductionmentioning
confidence: 85%
“…In recent years, a drastic decrease in sea ice has been reported for the western Arctic Ocean during the summer months, and even greater related changes in sea surface temperatures have been reported (Stroeve et al, 2007;Steele et al, 2008). The changes in sea surface temperatures, increases in the frequency and intensity of cyclones, and northward shifts from their tracks during the summer months as well as during other seasons have also been reported (Serreze et al, 2000;McCabe et al, 2001;Sepp and Jaagus, 2011).…”
Section: Introductionmentioning
confidence: 85%
“…Although NSTM heat is gained in the summer, the release of this heat often occurs in later seasons. Observations in the Canada Basin show that the NSTM often survives into fall, and that heat from this layer can be mixed into the surface mixed layer to delay or slow freeze up (Steele et al, 2008;Jackson et al, 2010;Steele et al, 2011;Timmermans, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although NSTM heat is gained in the summer, the release of this heat often occurs in later seasons. Observations in the Canada Basin show that the NSTM often survives into fall, and that heat from this layer can be mixed into the surface mixed layer to delay or slow freeze up (Steele et al, 2008;Jackson et al, 2010;Steele et al, 2011;Timmermans, 2015).Early studies of the NSTM during AIDJEX (Maykut and McPhee, 1995) and SHEBA (McPhee et al, 1998) found that the layer was present directly below the summer surface mixed layer, at depths between 25 and 35 m. However, the Canada Basin upper ocean is freshening (McPhee et al, 2009) Summer sea ice extent in the Western Arctic has decreased significantly in recent years resulting in increased solar input into the upper ocean. Here, a comprehensive set of in situ shipboard, on-ice, and autonomous ice-ocean measurements were made of the early stages of formation of the near-surface temperature maximum (NSTM) in the Canada Basin.…”
mentioning
confidence: 99%
“…6). Many Arctic regions cooled by 0.5°C per decade over 1930-1965 during a mostly negative phase of the Arctic Oscillation, while warming occurred over 1965-1995 when the Arctic Oscillation was mostly in a high phase (Steele et al, 2007).…”
Section: Physical Conditions and Circulation In The Arcticmentioning
confidence: 99%